A castle in wartime : one family, their missing sons, and the fight to defeat the Nazis - Bailey, Catherine, 1960- (Viking, 2019)
"An enthralling story of one family's extraordinary courage and resistance amidst the horrors of war from the New York Times bestselling author of The Secret Rooms. As war swept across Europe in 1940, the idyllic life of Fey von Hassell seemed a world away from the conflict. The daughter of Ulrich von Hassell, Hitler's Ambassador to Italy, her marriage to Italian aristocrat Detalmo Pirzio-Biroli brought with it a castle and an estate in the north of Italy. Beautiful and privileged, Fey and her two young sons lead a tranquil life undisturbed by the trauma and privations of war. But with Fascism approaching its zenith, Fey's peaceful existence is threatened when Ulrich and Detalmo take the brave and difficult decision to resist the Nazis. When German soldiers pour over the Italian border, Fey is suddenly marooned in the Nazi-occupied north and unable to communicate with her husband, who has joined the underground anti-Fascist movement in Rome. Before long, SS soldiers have taken up occupancy in the castle. As Fey struggles to maintain an air of warm welcome to her unwanted guests, the clandestine activities of both her father and husband become increasingly brazen and openly rebellious. Darkness descends when Ulrich's foiled plot to kill the Fuhrer brings the Gestapo to Fey's doorstep. It would be months before Detalmo learns that his wife had been arrested and his two young boys seized by the SS."--